High K Low Loss Dielectrics Co-Fireable with LTCC - Christina Modes; Stefan Malkmus; Frieder Gora (Active and Passive Electronic Components)
Rapid growth in the application of LTCC technology for RF wireless is clearly driven by the trend of miniaturization and mobile communication systems. This technology provides the possibility of integration of passive components in a cost effective way. Heraeus has implemented compatible high permitivity and low loss dielectrics with NPO performance into modified Heraeus CT700 low temperature co-fired ceramic tape system. The majority of commercially available microwave dielectrics show increasing firing temperatures >200 °C which make them incompatible with Ag metallizations or show high dielectric loss which limit their usage in RF wireless applications. This development work demonstrates the integration of a low loss, high permittivity ε=60 dielectric tape into a conventional Ag bearing LTCC structure. The concept of a dual sintering process is introduced and the resultant mechanical benefits with regard to tape fired shrinkage are explained in detail. Permittivity and dielectric loss data at RF for the new structure are presented. These high K and low loss dielectrics along with a comprehensive material system developed by Heraeus will support customers in meeting the challenges of reducing cost and enhancing the performance of RF devices for high frequency applications.